Enhancing Work Ethic and Alleviating Boredom Among Crew Members of Korean Vessel Owners' Motor Vessels Through the Appreciation of Aesthetic Objects - S.Sn., M.Pd., Lilies Lestari, (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2025)
Working as a sailor or crew member on the Fosep Engine Vessel owned by a Korean entity entails a significant risk of occupational stress. The crew members often spend approximately six months annually working and residing away from home in a distinctive work setting. Moreover, fluctuating internal circumstances aboard the vessel and diverse worker histories may induce occupational stressors. Determinants of work-related stress are essential for enhancing appreciation and aesthetic interest in aesthetic objects, thereby influencing routine behavior and entertainment, which ultimately fosters a more optimal work ethic and mitigates boredom among the crew members on the Fosep Engine Vessel owned by a Korean entity. This study aims to explore an artistic approach to relaxation in employee psychological therapy, with the anticipated results serving as a reference for interdisciplinary collaboration in the realms of art and maritime work, ultimately enhancing work ethic and alleviating employee stress. The employed research methodology is qualitative, utilizing data gathering techniques such as surveys, questionnaires, observations, and interviews, alongside triangulation analysis methods to derive conclusions from the findings. This study concludes that art serves as a vehicle for individuals to articulate emotions, thoughts, and experiences, providing enjoyment during work-related boredom, therefore enhancing work ethic and alleviating employee stress. Artistic entertainment may serve as a means to regulate emotions, allowing the mind to govern kinesthetic possibilities, sensory experiences, and symbolic interpretations, so facilitating expressive communication.